2020
DOI: 10.1002/asia.202000384
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Laser Deposition‐based Thin Film Microbatteries

Abstract: Emerging applications for robust small format or distributed devices feature a need for power and rechargeable lithium-ion batteries could play a significant role. This review focuses on a high precision technique to controllably grow thin-film electrodes or full all-solid-state batteries, that is, pulsed laser deposition (PLD). The technique and solidstate batteries are introduced followed by a detailed showcase of the depth of PLD-based growth undertaken on cathodes, electrolytes, anodes and whole microbatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 321 publications
0
33
0
Order By: Relevance
“…These batteries can only be used for low-power applications owing to their thin film nature; in addition, the deposition technique used for fabricating these devices is expensive compared with the traditional slurry coating method used to manufacture Li batteries. Despite these limitations, after Oudenhoven et al [ 117 ] proposed the concept and design of 3D microbatteries, the use of thin-film electrolytes for microelectronic applications has been explored by many researchers [ 504 , 505 , 506 , 507 , 508 , 509 , 510 , 511 , 512 , 513 , 514 , 515 , 516 , 517 , 518 , 519 , 520 , 521 ].…”
Section: Oxide Solid Electrolytesmentioning
confidence: 99%
“…These batteries can only be used for low-power applications owing to their thin film nature; in addition, the deposition technique used for fabricating these devices is expensive compared with the traditional slurry coating method used to manufacture Li batteries. Despite these limitations, after Oudenhoven et al [ 117 ] proposed the concept and design of 3D microbatteries, the use of thin-film electrolytes for microelectronic applications has been explored by many researchers [ 504 , 505 , 506 , 507 , 508 , 509 , 510 , 511 , 512 , 513 , 514 , 515 , 516 , 517 , 518 , 519 , 520 , 521 ].…”
Section: Oxide Solid Electrolytesmentioning
confidence: 99%
“…Such methods of deposition as sputtering, 60,194 ebeam evaporation, 190 sol-gel, 149 spin-coating, 195 PLD 186,196 and ALD were applied to produce thin-lm crystalline electrolytes, and various preparation conditions were reviewed. 29,44,149,197,198 The other new deposition methods, for instance, for LLZO, are currently under development and optimization as discussed above. 147,148 Up to now, it was observed that the higher e-beam evaporation power (600 W) applied for the LLTO fabrication resulted in a higher ionic conductivity.…”
Section: Perovskitementioning
confidence: 99%
“…281 Other techniques, like PLD and ALD, are gaining more attention in LiPON studies due to the promising results, and these techniques' features are discussed in the recent reviews by Julien et al, 29 and Liu et al, 43 Meng et al, 44 Fenech and Sharma. 198 In short, for PLD, the importance of N 2 gas pressure and laser uence was highlighted so far, 266 while for ALD, the precursors and the temperature window were mentioned to be important parameters. 43,44 Thorough studies on PLD/ALD conditions and their impact on LiPON's direct performance in the microbatteries are still limited.…”
Section: Lithium Phosphate Based Electrolytesmentioning
confidence: 99%
“…(A) Thermal evaporation, S. Babar, CC BY-SA 3.0, via Wikimedia Commons, (B) sputter deposition using Ar gas, Sigma-Aldrich, CC BY-SA 4.0, via Wikimedia Commons, (C) pulsed laser deposition, (D) electron beam evaporation, Jatosado, CC BY-SA 3.0, via Wikimedia Commons. Teng et al, 2018;Yu et al, 2018;Fenech and Sharma 2020). However, only few have actually fabricated ASTBs with thin-film solid electrolytes using PLD techniques (Huang et al, 2003;Huang et al, 2004;Kuwata et al, 2004;Baskaran et al, 2009;Matsuda et al, 2018).…”
Section: Pulsed Laser Depositionmentioning
confidence: 99%